An examination of the level of engagement of modern portfolio techniques for portfolio management by real estate firms in Lagos State, Nigeria. Issue 1 (1st March 2022) - Oloke, O.C.; Odetunmbi, O.A.; Akinwumi, S.A.
Abstract: Portfolio management in real estate practices was examined in this study with a view to ascertaining the techniques engaged in carrying out the risk and return analysis as well as the evaluating portfolio performance in the firm. Questionnaires were administered to respondents from 208 estate surveying and valuation firms in Ikeja, Lagos Island, Ikoyi and Victoria Island, Lagos State.Response rate achieved was 86.5%. Basic descriptive tools of percentage, weighted mean, relative importance index were used to analyse the data.The study found that the number of firms that offer portfolio management services is rather low compared to other areas of services.Results further showed that the firms ranked discounted cashflow and contemporary growth models higher than the modern portfolio techniques for asset return assessment whereas simulation and modern portfolio tools ranked higher among the techniques for risk assessment. Finally, the results showed that most firms make use of contemporary growth models, benchmark, style or market comparison to evaluate the performance of the portfolio. The study therefore suggests that estate firms embark on staff capacity development for effective application of modern portfolio theory techniques and making the service widespread among practicing firms.